USING MARKETING STRATEGIES TO INCREASE SALES ON ONLINE SHOPPING AREAS (Marketing Journal, 2025)
The article analyzes the impact of ma rketing strategies on product sales in online marketplaces. It examines the freemium model, live -streaming sales, omni -digital strategies, use of artificial intelligence, and market segmentation. The findings help companies attract new customers, increase sales, and strengthen brand reputation.
Keywords: marketing strategy; online trade; freemium model; live -streaming; artificial intelligence; market analysis